Cellular cap-binding proteins associate with influenza virus mRNAs. - Bier, K; York, A; Fodor, E (2011)
The influenza virus RNA polymerase synthesizes three types of RNA: genomic vRNA, anti-genomic cRNA and mRNA. Both vRNA and cRNA are bound by the viral RNA polymerase and nucleoprotein to form ribonucleoprotein complexes. Viral mRNAs are also proposed to be bound by the RNA polymerase to prevent their endonucleolytic cleavage, regulate the splicing of M1 mRNA, and facilitate translation. Here, we used standard immunoprecipitation, biochemical purification and RNA immunoprecipitation assays to investigate the association of viral and host factors with viral mRNA. We found that viral mRNA associates with the viral non-structural protein 1 (NS1), cellular poly(A)-binding protein 1 (PABP1), the 20 kDa subunit NCBP1 of the nuclear cap-binding complex (CBC), the RNA and export factor-binding protein REF/Aly and the translation initiation factor eIF4E. However, our data suggest that the RNA polymerase might not form part of the viral messenger ribonucleoprotein (mRNP) complex. We propose a model in which viral mRNAs, by associating with cellular cap-binding proteins, follow the pathways normally used by cellular mRNAs for splicing, nuclear export and translation.